Current status of robotic surgery for liver transplantation - Dai Hoon Han (Society of Gastrointestinal Intervention, 2022)
Successfully performing laparoscopic procedures in donor hepatectomy provides better quality of life and minimizes surgical complications for the donor. However, only a few experienced institutions can perform laparoscopic donor hepatectomy, which has a long learning curve and unergonomic surgical conditions. Meanwhile, robotic surgical systems have advanced to the point that they can compensate for the limitations of laparoscopic surgical systems. A robotic system provides a steady and magnified three-dimensional visualization with a wide range of motion and tremor-free instrumentation. Due to the benefits of robotic systems, robotic donor hepatectomy has been successfully performed in recent years. Therefore, the aim of this review is to present the current circumstances regarding the use of robotic systems in liver transplantation.